Is it Parental Communication, Self-Esteem, or Internet use that makes Pornography Behavior in Teenagers? (cases of pornography and porno-action) - Mahsiani Mina Laili; Herien Puspitawati; Lilik Noor Yuliati (Journal of Child Development Studies, 2018)
Parent-adolescent communication will affect both positive and negative behaviors in adolescents. This study aims to analyze the influence of the characteristics of adolescents and families with parent-adolescent communication, self-esteem, the use of internet, pornography and porn-action.The respondents of the study were teenagers in the age groups of 14-17 years, consisted of 137 respondents in Bogor, selected by using random sampling technique.Parent-adolescent communication consists of daily communication and preventife discussion of pornography and porn-action.Furthermore, adolescent' self-esteem includes both positive and negative perceptions of self among adolescents. The use of the media is focused on the frequency of Internet use for pornography and porn-action behavior including viewing and disseminating porn contents. Data were analyzed with independent sample t-test, and multiple linear regression test. The results showed that female are more open to communicate with parents than male. Male pornography and pornoaction behavior are higher than female. Regression results indicate that preventative discussion of pornography and porn-action of parent-adolescents and internet usage affect the behavior of pornography and porn-action.